Feasibility Test of Osteichthyes Wet Preparations through the Utilization of Chitosan on Storage Quality as Practical Media for Vertebrate Zoology - Muhamad Kurnia Sugandi; Putut Marwoto; Sunyoto Eko Nugroho (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to evaluate the use of chitosan as a substitute for formalin in making wet preparations of true bony fish (Osteichthyes) and to assess the feasibility of storing them as practicum media in the Vertebrate Zoology course. Osteichthyes body size varies from 1 cm to 6 meters. The main characteristic of Osteichthyes is the presence of a skeleton consisting of native bone and a hard calcium phosphate matrix. The skin is protected by various types of scales, including ganoid, cycloid, or stenoid scales. The research method used is Experimental Research Method with descriptive approach, which includes hedonic test and shelf life test (organoleptic) through panelist participation. Tilapia (Oreochromis niloticus) was used as the specimen in this experiment with variations in chitosan concentration of 0.50, 1.50, 2.50, and 3.50%. The study included evaluation of Osteichthyes wet preparations by considering aroma and odor, texture, color, as well as monitoring storage stability for one week. The results showed that the wet preparation using chitosan concentration of 3.5% gave satisfactory results for the observation of Osteichthyes structure. In addition, the storage evaluation showed that the quality of the preparations could be well maintained over a certain period. This indicates that chitosan can be an effective alternative in making Osteichthyes wet preparations for Zoology practicum